Bidirectional SAR Imaging Mode - Mittermayer, Josef; Wollstadt, Steffen; Prats-Iraola, Pau; Lopez-Dekker, Paco; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2013)
The paper introduces the Bi-Directional (BiDi) SAR imaging mode, i.e. the simultaneous imaging of two directions by one antenna into one receiving channel, and presents short-term time series of images and interferograms acquired by the TerraSAR-X and TanDEM-X satellites. A comparison to alternative approaches for the acquisition of short-term time series is provid-ed. The BiDi acquisition geometry is defined and a TerraSAR-X bi-directional antenna pattern is analyzed. BiDi raw data are simulated, sampled with different PRF values and compared to real BiDi raw data. The spectral separation of simultaneously acquired forward and backward looking images is explained. The paper presents the image results of BiDi acquisitions with Ter-raSAR-X and TanDEM-X satellites flying with 20 km along-track separation. This pursuit configuration allowed for the acquisition of up to six short-term repeated images and up to three interferograms in a single pass. An overview of potential applications for the new bi-directional SAR imaging mode concludes the paper.
DLR Import::2019-04-02
Keywords: Bidirectional synthetic aperture radar (BiDi SAR); TanDEM-X; TerraSAR-X